Teknik Interpolasi Bikubik untuk Memperbesar Gambar Hasil Pemetaan Suhu dari Sensor MLX90640 pada Praktikum Mikrokontroller - Mochammad Darwis (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
The occurrence of various disruptions and damage to equipment and electrical installations begins with a significant temperature increase in it. The temperature increasing in electrical equipment and installations will also increase the consumption of energy or power required. Previous technology used a temperature sensor and current sensor which had to be installed in the environment to be monitored. The temperature measurement system without touching the surface which is measured using infrared rays is a new breakthrough that really helps maintenance and repair. Also with the existence of a temperature sensor arranged in an array, it can map the existing temperature so that it can provide a better picture for analyzing the symptoms that  occur, compared  to using a temperature sensor that measures one point only. A temperature imaging camera is currently very expensive, making procurement a bit difficult for laboratories dealing with electrical equipment and installations. In this research, we will try to make an inexpensive temperature imaging camera using the MLX90640 sensor and the ESP32 microcontroller. Bicubic interpolation is used to  enlarge the resulting image obtained  by the MLX90640 sensor. The MATLAB program is   used to simulate and create an overall temperature imaging camera system. Tested and compared with two other interpolation methods to ensure that bicubic interpolation can produce better magnified images.